A milling steel fiber and its application in ultra-high performance concrete and wear-resistant floor
By using high-strength and high-toughness milling steel fibers, the problems of low tensile strength and poor toughness of micro-wire steel fibers in ultra-high performance concrete are solved, the initial crack strength and crack resistance are improved, the structural life is extended, and the resistance of micro-wire steel fibers is resistant to the high performance concrete. The impact resistance is enhanced in the grinding floor.
Patent Information
- Application Number
- CN202110598886.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-05-31
AI Technical Summary
The tensile strength of micro-wire steel fibers in ultra-high performance concrete is too low, the fibers are too long and the toughness is poor, which leads to rapid rust after initial cracking, reducing structural durability, and difficulty in exerting bonding performance, affecting the resistance to initial cracking.
High-strength and high-toughness milled steel fibers are made of arc-shaped or approximately rectangular cross-section, rough surface, end hooks on both ends, tensile strength is 1500~2500MPa, length is 12~22mm, and cross-section width is 2~3mm. The cross-sectional thickness is 0.2~0.4mm, and the bonding strength and mechanical choking force are improved through straight, arched or wavy structures, and the coordinated work with the concrete substrate is enhanced.
Significantly improve the initial crack strength and crack resistance of ultra-high performance concrete, extend the service life of the structure, enhance corrosion resistance, is suitable for complex environments, and enhance impact resistance in ultra-high performance concrete wear-resistant floors to reduce crack generation.
Smart Images

Figure CN115477486B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building engineering materials, and specifically relates to a milling steel fiber and application thereof in ultra-high performance concrete and ultra-high performance concrete wear-resistant floor. Background Art
[0002] Ultra-high performance concrete (UHPC) is a cement-based material based on close packing of aggregates and cementitious materials, low water-binder ratio, and steel fiber reinforcement. It has ultra-high strength, high toughness, and excellent durability. In recent years, it has been gradually applied in many engineering fields. Its maximum aggregate particle size is less than 8mm, usually the aggregate particle size is less than 2.36mm, its water-binder ratio is less than 0.24, and its compressive strength is not less than 120MPa.
[0003] The fiber cross-section of the microfilament steel fiber commonly used in ultra-high performance concrete is circular, with a diameter of 0.15-0.3mm, a length of 10-20mm, straight or hooked, and a tensile strength of ≥2000MPa; because the interfacial bonding strength is much lower than the tensile strength of the steel fiber, the microfilament steel fiber and the ultra-high performance concrete matrix do not work well together, and have almost no effect on the initial crack resistance of the ultra-high performance concrete. After the ultra-high performance concrete reaches the initial crack strength, the ultra-high performance concrete cracks, and the internal microfilament steel fibers will quickly rust in the natural environment, which greatly reduces the durability of the structure and makes it difficult for the high durability of the ultra-high performance concrete to play a role. It is urgent to develop methods that can improve the initial crack strength of ultra-high performance concrete.
[0004] The cross section of common milling steel fibers on the market is arc-shaped, with a rough inner arc surface and a smooth outer arc surface. The length is 30-34 mm, the cross-sectional width is 1.4-3.8 mm, the cross-sectional thickness is 0.1-0.4 mm, and the tensile strength is 700-1000 MPa. Its bonding strength with ordinary concrete is relatively high, but experiments in ultra-high performance concrete show that common milling steel fibers have the disadvantages of too low tensile strength, too long fibers, and poor toughness. When ultra-high performance concrete is destroyed, the fibers are pulled apart, making it difficult to exert its excellent bonding performance. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a milling type steel fiber.
[0006] The milling steel fiber of the present invention is used for ultra-high performance concrete, and has high strength, good toughness, rough surface and end hooks. Compared with microfilament steel fiber, it has the characteristics of high bonding strength and strong mechanical bite force; compared with ordinary milling steel fiber, it has the characteristics of high strength and high toughness, and can effectively improve the initial crack strength of ultra-high performance concrete.
[0007] Another object of the present invention is to provide an application of the above-mentioned milling steel fiber in ultra-high performance concrete and ultra-high performance concrete wear-resistant floor.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A milled steel fiber is obtained by milling high-strength steel ingots or steel plates, and includes a steel fiber body with an arc-shaped or approximately rectangular cross-section. The steel fiber body is straight, arched or wavy, with rough upper and lower surfaces or the entire surface, and end hooks at both ends.
[0010] Preferably, the tensile strength of the milled steel fiber is 1500-2500 MPa, and the milled steel fiber body has a rough surface, which greatly increases the contact area between the steel fiber and the cement matrix, thereby greatly improving the bonding strength between the steel fiber and the matrix; the end hooks at both ends further strengthen the anchoring force of the steel fiber, so that the mechanical properties of the steel fiber can be fully utilized, thereby improving the initial crack strength of the ultra-high performance concrete.
[0011] Preferably, the milled steel fiber has a length of 12 to 22 mm, a cross-sectional width of 2 to 3 mm, a cross-sectional thickness of 0.2 to 0.4 mm, and an end hook length of 1 to 2 mm.
[0012] Preferably, the steel fiber body is straight, and the length of the straight portion thereof is ≥ 2 / 3 of the total fiber length; the steel fiber body is arched, and the arch curvature is 25 to 45°, more preferably 25 to 35°; the steel fiber body is wavy, with 2 wave peaks and a wave height of 0.6 to 1.2 mm.
[0013] Preferably, the steel fiber body is straight with end hooks at both ends, the end hooks are in a broken line shape, and the straight part can be twisted, which greatly enhances the mechanical bite force of the steel fiber and thereby improves the interface bonding strength between the steel fiber and the matrix.
[0014] The arched steel fiber body has better wear resistance than the straight one, and can give full play to the toughness advantage of the fiber, improve its coordination with the concrete matrix, and achieve the purpose of strengthening and toughening.
[0015] The wavy steel fiber is provided with two wave peaks with a wave height of 0.6 to 1.2 mm, which increases the contact area between the steel fiber and the matrix, improves the bonding efficiency of the steel fiber, helps to achieve uniformity of anchoring force in all directions, and further enhances the anchoring force between the steel fiber and the matrix.
[0016] Preferably, the alloy steel material used for the milling steel fiber consists of the following components: Mn=7.3-9.9%, C=0.2-0.4%, Al=1.3-2.1%, S=0-0.016%, P=0-0.012%, and the remainder is Fe and unavoidable impurities.
[0017] Preferably, the surface of the milled steel fiber can also be subjected to anti-corrosion treatment. By preparing an anti-corrosion layer on the surface of the steel fiber body, the corrosion resistance of the steel fiber is greatly improved, so that it can be used in more complex and harsh environments.
[0018] The above-mentioned milling steel fiber is used in ultra-high performance concrete and ultra-high performance concrete wear-resistant floor.
[0019] Preferably, the application is: adding the milling steel fiber alone or mixed with the microfilament steel fiber into the ultra-high performance concrete and ultra-high performance concrete wear-resistant floor component, wherein the volume content of the milling steel fiber is 1-10%, and the volume content of the microfilament steel fiber is 0-4%.
[0020] More preferably, the volume content of the milling steel fiber is 1-6%, and the volume content of the microfilament steel fiber is 1-4%.
[0021] An ultra-high performance concrete wear-resistant floor comprises an ordinary concrete base, a reinforced steel grid and the above-mentioned milled steel fiber reinforced ultra-high performance concrete surface layer, wherein the volume content of the milled steel fiber is 1-6%, and the reinforced steel grid is located in the ultra-high performance concrete layer and connected to the ordinary concrete through a connector.
[0022] Preferably, the thickness of the milling steel fiber reinforced ultra-high performance concrete surface layer is 30 to 100 mm.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] (1) The milled steel fiber of the present invention has a rough surface, which greatly increases the contact area between the steel fiber and the ultra-high performance concrete matrix, thereby greatly improving the bonding strength between the steel fiber and the ultra-high performance concrete matrix.
[0025] (2) The tensile strength of the milled steel fiber described in the present invention is 1500 to 2500 MPa. By adopting a straight, arched or wavy structure with end hooks at both ends, the coordination between the steel fiber and the ultra-high performance concrete matrix can be improved, so that the mechanical properties of the steel fiber can be fully utilized, thereby improving the initial crack strength of the ultra-high performance concrete, giving full play to the toughness advantage of the steel fiber, and achieving the purpose of strengthening and toughening.
[0026] (3) The surface of the milled steel fiber of the present invention is subjected to anti-corrosion treatment, which greatly improves the corrosion resistance of the steel fiber, so it can be used in more complex and harsh environments.
[0027] (4) When the present invention is applied to the field of ultra-high performance concrete wear-resistant flooring, it can enhance the impact resistance of the wear-resistant flooring under fatigue without using an interlayer adhesive, and reduce the generation of small cracks and possible bulges under impact.
[0028] Based on the above characteristics, the milling steel fiber described in the present invention can effectively improve the crack resistance and impact resistance of ultra-high performance concrete, and is not prone to producing tiny cracks, thereby meeting the crack resistance and impact resistance requirements of ultra-high performance concrete under extreme environments and special requirements, extending the service life of the structure, and having significant economic, social and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of milling straight steel fiber in the present invention, in which: end hook 1, cross-section upper surface 2, cross-section lower surface 3.
[0030] Figure 2 It is a schematic diagram of milling arched steel fiber in the present invention, in which: end hook 1, inner arc surface 4 of cross section, outer arc surface 5 of cross section, and arch curvature α.
[0031] Figure 3 It is a schematic diagram of milling corrugated steel fiber in the present invention, in which: end hook 1 and wave crest 6.
[0032] Figure 4 Schematic diagram of the cross section of the milled steel fiber of the present invention, in Figure (a): the upper surface 2 and the lower surface 3 of the milled steel fiber with an approximately rectangular cross section; in Figure (b): the inner arc surface 4 and the outer arc surface 5 of the milled steel fiber with a circular arc cross section.
[0033] Figure 5 This is a schematic diagram of the overall structure of the milled steel fiber used for ultra-high performance concrete wear-resistant flooring in the present invention, in which: ordinary concrete base layer 9, reinforced steel grid 8, milled steel fiber reinforced ultra-high performance concrete surface layer 7, transverse steel bars 10, longitudinal steel bars 11, and short steel bars 12 for strengthening connections. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0035] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0036] Example 1
[0037] As attached Figure 1 and Figure 4(a) The milled steel fiber for ultra-high performance concrete has a straight appearance, a tensile strength of 1500 MPa, a length of 12 mm, a cross-section approximately rectangular with a width of 2.5 mm, a thickness of 0.2-0.4 mm, an end hook length of 1 mm, and is obtained by milling a steel plate. The alloy steel material composition is: Mn=7.5%, C=0.3%, Al=1.5%, S=0.012%, P=0.01%, and the remainder is Fe and unavoidable impurities.
[0038] Example 2
[0039] As attached Figure 2 and Figure 4 (b) The milled steel fiber for ultra-high performance concrete has an arched appearance, a tensile strength of 2000 MPa, a chord length of 22 mm, an arc-shaped cross-section, a width of 2 mm, a thickness of 0.2-0.4 mm, an end hook length of 2 mm, an arc angle α of 33°, and is obtained by milling a steel ingot. The alloy steel material composition is: Mn=8.0%, C=0.25%, Al=1.8%, S=0.008%, P=0.01%, and the remainder is Fe and unavoidable impurities.
[0040] Example 3
[0041] As attached Figure 3 and Figure 4 (b) The milled steel fiber for ultra-high performance concrete has a wavy appearance, a tensile strength of 2500 MPa, a length of 16 mm, an arc-shaped cross-section, a width of 3 mm, a thickness of 0.2-0.4 mm, an end hook length of 1.5 mm, and is provided with two wave peaks 6 with a wave height of 0.6 mm. It is obtained by milling a steel ingot, and the alloy steel material composition is: Mn=9.0%, C=0.2%, Al=2%, S=0.008%, P=0.01%, and the remainder is Fe and unavoidable impurities.
[0042] Comparative Example 1
[0043] The microfilament steel fiber used for comparison was provided by Guangdong Gatechi New Materials Co., Ltd. It is copper-plated straight, with a diameter of 0.22mm, a length of 13mm, and a tensile strength of 2700MPa.
[0044] The advantages of the present invention are reflected in the application of ultra-high performance concrete, so the steel fibers described in Examples 1-3 are added to ultra-high performance concrete and compared with Example 1 to analyze the difference in mechanical properties.
[0045] The following ultra-high performance concrete matrix uses 42.5R Portland cement, quartz sand with a maximum particle size of 1.18 mm, silica fume as undisturbed ash, polycarboxylate water-reducing agent, and tap water.
[0046] A total of 4 groups of ultra-high performance concrete mixes with different types of steel fibers were designed. The proportion of each group is given in Table 1. The weight proportion of each component is given. Table 2 shows the performance of each numbered milling steel fiber ultra-high performance concrete.
[0047] Table 1 Ultra-high performance concrete mix ratio
[0048] Serial number cement Silica Fume sand Water reducing agent water Steel Fiber 1. Microfilament steel fiber (Comparative Example 1) 800 200 1195 50 157 150 2. Milling of straight steel fibers (Example 1) 800 200 1195 50 157 150 3. Milling Arched Steel Fiber (Example 2) 800 200 1195 50 157 150 4. Milling of corrugated steel fibers (Example 3) 800 200 1195 50 157 150
[0049] Table 2 Ultra-high performance concrete properties
[0050] Serial number Initial crack strength (MPa) Compressive strength(MPa) Relative wear amount (%) 1. Microfilament steel fiber (Comparative Example 1) 9.2 150 100 2. Milling of straight steel fibers (Example 1) 11.3 161 88.5 3. Milling Arched Steel Fiber (Example 2) 12.1 157 87.1 4. Milling of corrugated steel fibers (Example 3) 12.8 159 89.3
[0051] Among the above four groups of ultra-high performance concrete, the initial crack strength of UHPC is greatly enhanced due to the good interface bonding performance between the milled steel fiber and UHPC, among which the initial crack strength of the wavy milled steel fiber is the highest.
[0052] Example 4
[0053] like Figure 5 As shown, the milling steel fiber for ultra-high performance concrete of the present invention can be used in the field of wear-resistant flooring, and the wear-resistant flooring includes a milling steel fiber reinforced ultra-high performance concrete surface layer 7, a reinforced steel grid 8, an ordinary concrete base layer 9, transverse steel bars 10, longitudinal steel bars 11, and short steel bars 12 for strengthening connections.
[0054] The mix proportions and properties of the ultra-high performance concrete in this embodiment are shown in Tables 1 and 2. The wear resistance test adopts the mass loss method according to the "Testing Procedures for Cement and Cement Concrete for Highway Engineering" (JTGE30-2005), and the size of the standard test piece is 150×150×150mm. Three groups of test pieces are made for each mix ratio and the average value is taken.
[0055] Pour ordinary concrete base, place the already tied reinforced steel grid, and quickly pour milling steel fiber reinforced ultra-high performance concrete to form a surface layer, where the thickness of the milling steel fiber reinforced ultra-high performance concrete surface layer is 80mm.
[0056] The specifications of the transverse steel bars 10 and the longitudinal steel bars 11 in the reinforced steel grid are both 12@200, the transverse steel bars 10 are U-shaped, and the longitudinal steel bars 11 are located at the U-shaped opening, which is suitable for milling steel fiber reinforced ultra-high performance concrete surface layers with a thickness of 60 to 100 mm.
[0057] As shown in Table 2, this embodiment reduces the mass wear of the wear-resistant floor under fatigue without using an interlayer adhesive by adding milling steel fibers into ultra-high performance concrete, and reduces the generation of small cracks and possible damage caused by impact.
[0058] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A milling steel fiber for ultra-high performance concrete, characterized in that: It is obtained by milling steel ingots. The steel fiber body is arched, with a tensile strength of 2000MPa, a chord length of 22mm, an arc cross section, a width of 2mm, a thickness of 0.2-0.4mm, an end hook length of 2mm, and an arc angle α of 33°; Or it is obtained by milling from a steel ingot. The steel fiber body is wavy, with a tensile strength of 2500MPa, a length of 16mm, an arc-shaped cross-section, a width of 3mm, a thickness of 0.2-0.4mm, a hook length of 1.5mm at the end, 2 wave peaks, and a wave height of 0.6mm.
2. The milled steel fiber according to claim 1, characterized in that The alloy steel material used for the milling steel fiber consists of the following components: Mn=7.3-9.9%, C=0.2-0.4%, Al=1.3-2.1%, S=0-0.016%, P=0-0.012%, and the remainder is Fe and inevitable impurities.
3. The milled steel fiber according to claim 1, characterized in that The surface of the milled steel fiber is subjected to anti-corrosion treatment, and an anti-corrosion layer is prepared on the surface of the steel fiber body.
4. Use of the milling steel fiber according to any one of claims 1 to 3 in ultra-high performance concrete and ultra-high performance concrete wear-resistant flooring.
5. The use of the milling steel fiber in ultra-high performance concrete and ultra-high performance concrete wear-resistant floor according to claim 4 is characterized in that: The milling steel fiber is added alone or mixed with the microfilament steel fiber into the ultra-high performance concrete and ultra-high performance concrete wear-resistant floor component, wherein the volume content of the milling steel fiber is 1-10%, and the volume content of the microfilament steel fiber is 0-4%.
6. The use of the milling steel fiber in ultra-high performance concrete and ultra-high performance concrete wear-resistant floor according to claim 5 is characterized in that: The milling steel fiber and the microfilament steel fiber are mixed and added to the ultra-high performance concrete and the ultra-high performance concrete wear-resistant floor component, wherein the volume content of the milling steel fiber is 1-6%, and the volume content of the microfilament steel fiber is 1-4%.
7. An ultra-high performance concrete wear-resistant floor, characterized in that: It comprises an ordinary concrete base, a reinforced steel grid and a milled steel fiber reinforced ultra-high performance concrete surface layer, wherein the volume content of the milled steel fiber is 1 to 6%, the reinforced steel grid is located in the ultra-high performance concrete surface layer and is connected to the ordinary concrete base layer through a connecting piece, the milled steel fiber is the milled steel fiber according to any one of claims 1 to 3, and the thickness of the milled steel fiber reinforced ultra-high performance concrete surface layer is 30 to 100 mm.